Determine the equation of the function that has the indicated transformation applied to the function
f(x) = 3(x + 1)2 - 2. (2 marks each)
For a. I wrote f(x)=3(x-1)^2
For b. I wrote f(x)= - ___ (x+1)^2 -2
I'm getting really confused with what that blank should be filled with..
f(x) = 3(x + 1)2 - 2. (2 marks each)
- translated up 2 and moved 2 units to the right.
- reflected in the x-axis and stretched by a factor of 3.
For a. I wrote f(x)=3(x-1)^2
For b. I wrote f(x)= - ___ (x+1)^2 -2
I'm getting really confused with what that blank should be filled with..